Survival of patients treated with radiation therapy for anaplastic astrocytoma - Barker Christopher A.; Beal Maria Chang, Kathryn; Chan Timothy A. (Radiology and Oncology, 2014)
Background. Anaplastic astrocytoma (AA) represents 7% of primary brain tumors in adults. Patient-, tumor-, and treatment-related factors are thought to be predictive of survival. We retrospectively assessed the association of patient-, tumor-, and treatment-related factors with survival in AA treated with radiotherapy (RT) at our institution.